Tribological and Acoustic Performance of Luffa acutangula Fiber and Sal Wood Sawdust Reinforced Epoxy Composites: An Experimental Study - Nashmi H. Alrasheedi; Sivasubramanian Palanisamy; Veeranan Arunprasad; Barun Haldar; Durairaj Thresh Kumar (BioResources)
Hybrid epoxy composites reinforced with Luffa acutangula fiber (LAF) and Sal wood sawdust (SWD) were examined for their tribological and acoustic properties. A consistent 20 wt% LAF was employed throughout all composites, with the SWD content adjusted to 0%, 5%, 15%, and 25%.  The engineered composites underwent assessment for wear loss, coefficient of friction (CoF), sound absorption coefficient, and noise reduction coefficient. The results demonstrated a notable reduction in wear loss with the addition of SWD up to 15 wt%, with the 20FL/15SWD sample exhibiting the lowest wear at 0.32%. In a similar manner, the CoF decreased to 0.26 for the identical composition, indicating an ideal equilibrium between filler dispersion and fiber-matrix interaction. The enhancement of sound absorption and noise reduction coefficients was observed with increased SWD content, reaching peaks of 0.23 and 0.13, respectively for the 20FL/15SWD composite. The enhancements observed can be linked to the superior void-filling capacity and interfacial bonding facilitated by the SWD particles. Nonetheless, a high concentration of SWD (25 wt%) led to a minor decrease in performance attributed to particle agglomeration. The findings indicate that the 20FL/15SWD composite demonstrates enhanced tribo-acoustic performance, positioning it as a strong contender for applications requiring noise insulation and wear resistance.